Preliminary Validation of the Triana Test: A New Story Recall Test Based on Emotional Material. (18th June 2021) - Luque-Tirado, Andrea; Rodrigo-Herrero, Silvia; Sánchez-Arjona, María Bernal; Franco-Macías, Emilio
Objective: To first validate the diagnostic accuracy of the "Triana Test, " a new story recall test based on emotional material. Method: A phase I study of validation. We included 55 patients with amnestic Mild Cognitive Impairment and 69 healthy controls, diagnosed according to the "Memory Associative Test of the district of Seine-Saint-Denis" (TMA-93), and matched by age, gender, and educational level. The Triana Test's diagnostic accuracy was calculated by ROC curve analysis and Spearman correlations estimated its convergent validity with a hippocampal memory test, the Free and Cued Selective Reminding Test with Immediate Recall (FCSRT+IR). Results: The "Triana Test" immediate and delayed recalls showed adequate diagnostic accuracy (AUC ≥ 0, 74). The delayed free recall showed the highest diagnostic accuracy (AUC = 0.86). Correlations with the FCSRT+IR were moderate to strong. Conclusions: The "Triana Test" demonstrated accuracy for discriminating amnestic Mild Cognitive Impairment patients from healthy controls and convergent validity with the FCSRT+IR.